Solid Contact Potentiometric Sensors Based on a New Class of Ionic Liquids on Thiacalixarene Platform - Padnya, Pavel L.; Porfireva, Anna V.; Evtugyn, Gennady A.; Stoikov, Ivan I. (Frontiers in Chemistry, 2018)
New solid-contact potentiometric sensors have been developed for hydrogen phosphate recognition on the basis of ionic liquids containing tetrasubstituted derivatives of thiacalix[4]arene in cone and 1,3-alternate conformations with trimethyl- and triethylammonium fragments at the lower rim substituents. The recognition of selected anions including carbonate, hydrogen phosphate, perchlorate, oxalate, picrate, and EDTA was conducted using electrochemical impedance spectroscopy with ferricyanide redox probe. For the potentiometric sensor assembling, the ionic liquids were stabilized by multiwalled carbon nanotubes and carbon black deposited on the glassy carbon electrode. The influence of support, steric factors and modification conditions on the sensor performance has been investigated. As was shown, potentiometric sensors developed make it possible to selectively determine hydrogen phosphate anion within the concentration range from 1×10-2 to 1×10-6 M and limit of detection of 2×10-7 – 1×10-6 M with unbiased selectivity coefficients varied from 1.2×10-1 to 1.0×10-8 (carbonate, acetate, oxalate, succinate, glutharate, glycolate and malonate anions).